1982
DOI: 10.1021/i100008a007
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Stefan-Maxwell equations to diffusion in ion exchangers. 1. Theory

Abstract: Starting with the Stefan-Maxwell equations, general expressions for the ionic flux rates for binary exchange in ionsxchange resins have been developed. These equations have been shown to reduce to the Nernst-Planck equations exactly only as the concentration of either exchanging ion approaches unity. Furthermore, the single-ion diffusion coefficients used in the Nernst-Planck equations are shown to be certain combinations of the Stefan-Maxwell interaction coefficients. Most importantly, these combinations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…The phenomenological coefficients in irreversible thermodynamics and the MS diffusion coefficients can in fact be theoretically related to one another [17][18][19]. It has been shown, however, that the MS coefficients are less dependent on composition (total dissolved solids, as well as the different ions present) than are the phenomenological coefficients [20].…”
Section: Existing Electrodialysis Modelsmentioning
confidence: 99%
“…The phenomenological coefficients in irreversible thermodynamics and the MS diffusion coefficients can in fact be theoretically related to one another [17][18][19]. It has been shown, however, that the MS coefficients are less dependent on composition (total dissolved solids, as well as the different ions present) than are the phenomenological coefficients [20].…”
Section: Existing Electrodialysis Modelsmentioning
confidence: 99%
“…The fixed ionic group concentration is defined with the logistic function as presented in Eq. (13) in which x 0 is zero and the slope of the curve is chosen 120. The slope of the curve defined the thickness of the transition state in the logistic function.…”
Section: Model Approach and Assumptionsmentioning
confidence: 99%
“…Also, virtually, no data exist in the literature that compares the performance of mono-and bilayer cation-selective membranes especially at high current densities. There are various methods to model ion transport in ion-exchange membranes, and these have been reviewed and modeled by several authors [11][12][13]. In our earlier paper [14], we developed a NernstPlanck model of multicomponent ion transport through a cation-exchange membrane for a monolayer membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The theory has been applied to determine activity coefficients in dilute electrolyte solutions and the results are valid only in the limit of infinite dilution due to the neglect of shortrange interaction forces between ions in concentrated electrolyte solutions (Newman, 1991;Phto and Graham, 1986). In comparing the commonly used form of the electrolyte diffusion equations derived from the theory of irreversible thermodynamics with the Stefan-Maxwell Equations (4.8), Graham and Dranoff (1982) found that the Stefan-Maxwell diffusion coefficients were (a) less concentration dependent than the phenomenological coefficients of irreversible thermodynamics and (b) less dependent on the presence of other ions in the system. Pinto and Graham (1986) relate the StefanMaxwell coefficients to the viscosity of the solution and limiting ionic nobilities; they state that "the coefficients of the Stefan-Maxwell equations, unlike the coefficients of other flux equations, can be individually identified with physical phenomena occurring during the diffusion process.…”
Section: Mixtures Of Charged Species mentioning
confidence: 99%
“…Some advantages of using the Stefan-Maxwell formulation (Lightfoot et al, 1962;Riede and Schliinder, 1991, p. 611;Krishna and Wesselingh, 1997, p. 869;Pinto and Graham, 1986;Graham and Dranoff, 1982) where f12 (defined as the force required to give species 1 a speed of unity, i.e., force per unit speed) is the friction coefficient of a solute (designated species 1) in a solvent (designated species 2), k is the Boltzmann constant, and T is the temperature. where Rz is the radius of the solvent species; similarly when species 1 is the solvent and species 2 is the solute then the analogous formula (Wesselingh and Bollen, 1997) is:…”
Section: Introductionmentioning
confidence: 99%